2012
DOI: 10.1001/jama.2012.250
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab in Patients With Hereditary Hemorrhagic Telangiectasia and Severe Hepatic Vascular Malformations and High Cardiac Output

Abstract: EREDITARY HEMORRHAGIC telangiectasia (HHT) (Online Mendelian Inheritance in Man [OMIM] #187300) is a dominantly inherited genetic vascular disorder characterized by recurrent epistaxis; cutaneous telangiectasia; and visceral arteriovenous malformations (AVMs) that affect many organs, including the lungs, gastrointestinal tract, liver, and brain. Diagnosis is based on the Curaçao criteria and is considered definite if at least 3 of 4 criteria are fulfilled. 1 The criteria are spontaneous and recurrent epistaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
248
0
18

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(286 citation statements)
references
References 31 publications
(35 reference statements)
6
248
0
18
Order By: Relevance
“…2,3 Bevacizumab, a VEGF inhibitor, has been shown to reduce epistaxis, telangiectasias, and the need for iron infusions due to stabilized hemoglobin (Hgb). [3][4][5][6][7][8][9][10] Additionally, there has been marked improvement in symptoms and transfusion requirements. Other reports demonstrated improvement in symptoms and transfusion requirements without an appreciable change in AVMs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Bevacizumab, a VEGF inhibitor, has been shown to reduce epistaxis, telangiectasias, and the need for iron infusions due to stabilized hemoglobin (Hgb). [3][4][5][6][7][8][9][10] Additionally, there has been marked improvement in symptoms and transfusion requirements. Other reports demonstrated improvement in symptoms and transfusion requirements without an appreciable change in AVMs.…”
mentioning
confidence: 99%
“…4,6 DupuisGirod et al showed that bevacizumab administration is associated with improvement in high output cardiac failure, secondary to its effect on liver capillaries and arteriovenous shunting. 5,7 In the previously reported cases, the dose of bevacizumab varied from 5 mg per kilogram (mg/kg) body weight 1,4-10 to 10 mg/kg body weight 3 administered every 2 weeks (table 1). The elimination half-life of bevacizumab has been determined to be 18 to 20 days; however, in the study done by Dupuis-Girod et al 5 it was found to be 21.5 days.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Бе вацизумаб является одним из таких препаратов. Он ингибирует биологическую активность фактора роста эндотелия сосудов (VEGF) и применяется в настоя щее время как химиотерапевтический препарат [79].…”
Section: лечениеunclassified
“…Taking into account some literature reports, describing positive effects of bevacizumab [2][3][4] -following the patient's consent and having got a permission of the Bioethical Commission of the District Chamber of Physicians for the use of an "off-label" drug, totally 6 i.v. injections of 200 mg doses of bevacizumab were administered during the period from February to May 2014 in the 3-week intervals.…”
Section: Case Descriptionmentioning
confidence: 99%